2009
DOI: 10.1371/journal.pone.0008384
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Regulated Genes in Human Prostate Xenografts in Mice: Relation to BPH and Prostate Cancer

Abstract: Benign prostatic hyperplasia (BPH) and prostate carcinoma (CaP) are linked to aging and the presence of androgens, suggesting that androgen regulated genes play a major role in these common diseases. Androgen regulation of prostate growth and development depends on the presence of intact epithelial-stromal interactions. Further, the prostatic stroma is implicated in BPH. This suggests that epithelial cell lines are inadequate to identify androgen regulated genes that could contribute to BPH and CaP and which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…19,20 Hyperplastic growth of the prostate transition zone associated with clinical benign prostatic hyperplasia may be the result of the abnormal expression of key androgen-responsive genes, which lead to an imbalance between cell division and death. 44 Genes regulated by androgenic hormones are of critical importance for the normal physiological function of the human prostate gland, and they contribute to the development and progression of prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Hyperplastic growth of the prostate transition zone associated with clinical benign prostatic hyperplasia may be the result of the abnormal expression of key androgen-responsive genes, which lead to an imbalance between cell division and death. 44 Genes regulated by androgenic hormones are of critical importance for the normal physiological function of the human prostate gland, and they contribute to the development and progression of prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the pronounced androgen dependency of prostate tissue (Love et al 2009), it was of interest to investigate the expression of cGMP pathway proteins in this tissue under conditions of androgen ablation.…”
Section: Elucidation Of a Prostate-specific Androgen Regulationmentioning
confidence: 99%
“…PRKG1 was localized to stromal areas of the transition zone (Kedia et al 2008) but is not immunohistochemically detectable in epithelial cells (D Mü ller, A K Mukhopadhyay, M S Davidoff & R Middendorff, unpublished results). Thus, PRKG1 is expressed in those areas where androgens are thought to regulate prostate stem cell homeostasis and to maintain a growthquiescent adult prostate gland (Love et al 2009). As advanced age is the most important risk factor for the development of benign prostatic hyperplasia and prostate cancer (Sampson et al 2007), the identified agerelated increase in PRKG1 may have pathophysiological significance.…”
Section: Age-related Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PMEPA1 gene has been shown to suppress the androgen receptor (AR) and TGF-β signaling pathway and is abnormally expressed in prostate tumors (Liu et al, 2011). Besides, PTGDS and PTGER2 have been reported as AR-regulated or involved in prostate cancer (Love et al, 2009).…”
Section: Discussionmentioning
confidence: 99%